Join IDNLearn.com today and start getting the answers you've been searching for. Find the information you need quickly and easily with our reliable and thorough Q&A platform.


I'm so sorry for asking about this, I know I know how to solve this, but my mind keeps pulling a blank, please help!

Solve the following system of equations algebraically: y = -x - 3 2x - y = 6​


Sagot :

Answer:

add like terms

y=-3+1x-y=6

ok, umm 3 times 2= 6 right? don’t know why there are two = signs try plus -y to positive y and that would give you

y=-3+1x+6

i hate trying to solve these algebraically

hope this got you somewhere

Step-by-step explanation: